Bringing New Ph.D.s Together for Interdisciplinary Climate Change Research: DISCCRSSymposiumVII; Colorado Springs, Colorado; 13–20 October 2012. (29th January 2013) - Phelan, Liam; Jones, Holly; Marlon, Jennifer R.
Abstract : Climate change is complex and thus requires interdisciplinary research, and new scholars are rising to that challenge. The Dissertations Initiative for the Advancement of Climate Change Research (DISCCRS (pronounced "discourse"); see http://www.disccrs.org) brings together select groups of recent PhD graduates to encourage interdisciplinary work on climate change. The DISCCRS Symposium VII held just outside of Colorado Springs, Colo., brought together 33 graduates from fields as diverse as climatology, ecology, anthropology, and political science for an intensive week of cross‐disciplinary engagement in activities like facilitation and leadership training, collaborative research development, peer networking, communication training, and analysis of working group processes.